Spontaneous ureteric rupture due to high pressure chronic retention. Issue 3 (March 2022) - Deen, Shameer; Ogbu, Emmanuel; Walker, Nicholas Faure; Nkwam, Nkwam Michael
Summary: Spontaneous ureteric rupture is a rare phenomenon which can be traumatic or non-traumatic that may arise from ureteric obstruction, trauma, mucosal inflammation from urolithiasis, connective tissue disease or retroperitoneal fibrosis. High pressure chronic retention is characterised by noctural enuresis, a tense palpable bladder, hypertension, progressive renal impairment, bilateral hydronephrosis and hydroureter on imaging. Obstructive urological symptoms are typically absent in uncomplicated cases. We report the case of a 69-year-old male who presented with high pressure chronic retention and spontaneous ureteric rupture demonstrated on a noncontrast CT. This patient was managed with a urethral catheter on free drainage and a retrograde ureteric stent. The patient's condition improved, and the stent was removed after a uretero-pyeloscopy which revealed no extravasation. He later underwent a successful transurethral resection of the prostate.